2003
DOI: 10.1088/1126-6708/2003/10/023
|View full text |Cite
|
Sign up to set email alerts
|

Closed string field theory with dynamical D-brane

Abstract: We consider a closed string field theory with an arbitrary matter current as a source of the closed string field. We find that the source must satisfy a constraint equation as a consequence of the BRST invariance of the theory. We see that it corresponds to the covariant conservation law for the matter current, and the equation of motion together with this constraint equation determines the classical behavior of both the closed string field and the matter. We then consider the boundary state (D-brane) as an ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…We concentrate on the large negative ϕ region. In this region V Q+iP takes the form (11.7) and 30) where O L (P ) is an appropriate operator in the Liouville field theory which is even under P → −P . Thus the source terms are of the form 31) where |s X 0 ,g denotes some state in the X 0 and ghost CFT.…”
Section: D0-brane and Its Boundary State In Two Dimensional String Thmentioning
confidence: 99%
“…We concentrate on the large negative ϕ region. In this region V Q+iP takes the form (11.7) and 30) where O L (P ) is an appropriate operator in the Liouville field theory which is even under P → −P . Thus the source terms are of the form 31) where |s X 0 ,g denotes some state in the X 0 and ghost CFT.…”
Section: D0-brane and Its Boundary State In Two Dimensional String Thmentioning
confidence: 99%
“…This gives a general procedure for constructing the conserved charge carried by a D-brane corresponding to a specific rigid gauge transformation in closed string theory. The suggestion that the BRST invariance of B| carries information about conserved charges has been made earlier in [52].…”
Section: Symmetries To Conserved Charges In Open String Theorymentioning
confidence: 94%
“…They argued that the boundary state should transform under the closed string gauge transformation and found that the gauge invariance requires to add the Dirac-Born-Infeld (DBI) action to (1.1). The authors in [6] also considered a closed SFT with a source term representing a marginal deformation, namely (1.1). They pointed out that an (interacting) closed SFT requires a modification of the deformed boundary state; marginal deformations, which are expected to be solutions in open string theory, are no longer consistent solutions in open-closed string theory.…”
Section: Introductionmentioning
confidence: 99%